2021
DOI: 10.3390/ijerph18147214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gadolinium Deposits in the Cerebellum: Reviewing the Literature from In Vitro Laboratory Studies to In Vivo Human Investigations

Abstract: Gadolinium (Gd)-based contrast agents (GBCAs) are chemicals injected intravenously during magnetic resonance imaging (MRI) to enhance the diagnostic yield. The repeated use of GBCAs can cause their deposition in the brain, including the cerebellum. Such deposition may affect various cell subsets in the brain and consequently cause behavioral alterations due to neurotoxicity. Caution should thus be exercised in using these agents, particularly in patients who are more likely to have repeated enhanced MRIs durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…This has occurred in some cases to patients with chronic kidney disease, which developed nephrogenic systemic fibrosis (NSF), characterized by skin thickening and hyperpigmentation and extracutaneous fibrosis [ 15 , 16 , 17 ]. In addition, recent studies indicated that clinically developed GBCAs could be deposited in the brain after repeated use, and could cause neurotoxicity, although this has not been proven [ 18 , 19 ]. In both cases, tissue deposits of linear GBCAs are much higher than those of macrocyclic GBCAs.…”
Section: Introductionmentioning
confidence: 99%
“…This has occurred in some cases to patients with chronic kidney disease, which developed nephrogenic systemic fibrosis (NSF), characterized by skin thickening and hyperpigmentation and extracutaneous fibrosis [ 15 , 16 , 17 ]. In addition, recent studies indicated that clinically developed GBCAs could be deposited in the brain after repeated use, and could cause neurotoxicity, although this has not been proven [ 18 , 19 ]. In both cases, tissue deposits of linear GBCAs are much higher than those of macrocyclic GBCAs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the repeated administration of Gadolinium-containing contrast media has been generally debated [23,24]. While the use of contrast agents is essential in the initial MRI diagnosis of multiple sclerosis, their additional value in follow-up examinations is in doubt [25,26], and is considered optional, according to the current clinical guidelines in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, free Gd 3+ ions can cause nephrogenic systemic fibrosis (NSF) in patients with kidney diseases, resulting in the thickening and darkening of the skin and the reduction of organ function in the heart and lungs [ 22 , 29 , 30 ]. In addition, recent studies indicated that clinically developed Gd chelates could be deposited in the brain after repeated use and cause neurotoxicity [ 31 , 32 ]. SPION-based MRI contrast agents are more biocompatible than other metal-based NP contrast agents because iron is consumed in the human body as an essential element [ 33 ]; for example, iron is a central element in hemoglobin for oxygen binding.…”
Section: Introductionmentioning
confidence: 99%